Molecular Layer Deposition (MLD) of a Blocked Mercapto Silane on Precipitated Silica - Kim, S.; van Ommen, J. R.; Zara, D. La; Courtois, N.; Davin, J.; Recker, C.; Schoeffel, J.; Blume, A.; Talma, A.; Dierkes, W. K. (Organic Materials, 2023)
Chemically modified silica is widely used as a reinforcing filler in elastomers. The modification is generally done in situ while preparing the rubber. However, in order to increase the efficiency and facilitate the mixing process, the silica can be pre-treated by a 2-step molecular layer deposition. The precursors for the modification are 3-mercaptopropyl-triethoxysilane (MPTES) and octanoyl chloride (OC) to react with MPTES and form a blocked silane. The precipitated silica nanofiller was successfully treated with MPTES and showed a self-limiting behavior: saturation occurred at 2.7%. Furthermore, DRIFTS (diffuse reflectance infrared Fourier transform spectroscopy) analysis confirmed the successful deposition of MPTES on the silica surface by showing the -SH peak that appeared after the reaction of MPTES and silica. In the second step, OC was introduced to form a thioester on the surface of the MPTES-treated silica, controlling the reactivity of the mercapto group from MPTES by blocking it to prevent a negative influence on the processing behavior of the rubber. Thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy, and X-ray photoelectron spectroscopy (XPS) analytical results confirmed the deposition of the blocked mercapto silane on the silica. TGA results demonstrated the self-limiting behavior of OC, and DRIFTS and XPS proved the thioester formation. A thioester peak after the 2nd reaction step with OC appeared. At the same time, the disappearance of the -SH signal from the MPTES was observed, indicating the formation of the blocked mercapto silane structure. Transmission electron microscopy results showed that the treated silica has a well-distributed carbon and sulfur deposition after MPTES/OC treatment.
Keywords: precipitated silica; surface modification; molecular layer deposition